2017
DOI: 10.1111/add.13698
|View full text |Cite
|
Sign up to set email alerts
|

Testing bidirectional associations among emotion regulation strategies and substance use: a daily diary study

Abstract: Background and aims Alcohol and marijuana are widely used among college students. Emotion regulation strategies have been linked to alcohol and marijuana use but little attention has been devoted to modeling the directionality of these associations. Aims of the current study were to test whether (a) daytime use of emotion regulation strategies influences the likelihood of evening substance use and (b) evening substance use influences the likelihood of next-day use of emotion regulation strategies. Design Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 47 publications
2
31
0
2
Order By: Relevance
“…With regard to (the lack of) problem-solving skills, this is considered as mental flexibility in identifying adaptive solutions to problems encountered in everyday life [44]. Compared to individuals with no substance use disorder, individuals with substance use disorder reported a narrower range and poorer quality of problem-solving skills [44,45]. Specifically, Weiss et al [45] showed that more effective problem-solving strategies, along with greater daytime use of distraction, and reappraisal predicted lower evening substance use.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to (the lack of) problem-solving skills, this is considered as mental flexibility in identifying adaptive solutions to problems encountered in everyday life [44]. Compared to individuals with no substance use disorder, individuals with substance use disorder reported a narrower range and poorer quality of problem-solving skills [44,45]. Specifically, Weiss et al [45] showed that more effective problem-solving strategies, along with greater daytime use of distraction, and reappraisal predicted lower evening substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Weiss et al (2017) recently investigated the dynamic interplay between self-regulation and substance use by collecting daily-diary data from college student drinkers with no prior alcohol treatment experiences. They found that evening heavy drinking predicted lower odds of next-day problem-solving and higher odds of next-day avoidance (i.e., avoiding dealing with situation), and that evening marijuana use predicted lower odds of next-day problem-solving and higher odds of next-day cognitive reappraisal.…”
Section: A Contextual Model Of Self-regulation Change Mechanismsmentioning
confidence: 99%
“…However, we note some useful work‐arounds in the literature. For example, Weiss, Bold, Sullivan, Armeli, and Tennen () investigated the bidirectional associations between daily emotion regulation strategies and substance use in daily diary design. To do so, they simultaneously enquired about the current day's emotion regulation strategies (e.g., “since waking until the time of the report”), and substance use during the previous evening (e.g., “since completing yesterday's survey”), thus, allowing for lagged models to test these relations.…”
Section: Coping Measurement In Ambulatory Assessmentmentioning
confidence: 99%
“…Youth commonly cope with stressors in the form of negative cognitions (regarding the present or the future) or the recollection of past negative experiences. As such, a smaller subset of studies has measured adolescents coping responses to unpleasant internal experiences (Mori, Takano, & Tanno, ; Shahar & Herr, ; Weiss et al., ).…”
Section: The Process Of Coping: the Trigger And The Outcomementioning
confidence: 99%
See 1 more Smart Citation